Absorbable versus nonabsorbable sutures for the Krackow suture repair of acute Achilles tendon rupture: a prospective randomized controlled trial. (1st August 2022) - Park, Young H.; Kim, Woon; Choi, Jung W.; Kim, Hak J.
Abstract : Aims: Although absorbable sutures for the repair of acute Achilles tendon rupture (ATR) have been attracting attention, the rationale for their use remains insufficient. This study prospectively compared the outcomes of absorbable and nonabsorbable sutures for the repair of acute ATR. Methods: A total of 40 patients were randomly assigned to either braided absorbable polyglactin suture or braided nonabsorbable polyethylene terephthalate suture groups. ATR was then repaired using the Krackow suture method. At three and six months after surgery, the isokinetic muscle strength of ankle plantar flexion was measured using a computer-based Cybex dynamometer. At six and 12 months after surgery, patient-reported outcomes were measured using the Achilles tendon Total Rupture Score (ATRS), visual analogue scale for pain (VAS pain), and EuroQoL five-dimension health questionnaire (EQ-5D). Results: Overall, 37 patients completed 12 months of follow-up. No difference was observed between the two groups in terms of isokinetic plantar flexion strength, ATRS, VAS pain, or EQ-5D. No re-rupture was observed in either group. Conclusion: The use of absorbable sutures for the repair of acute ATR was not inferior to that of nonabsorbable sutures. This finding suggests that absorbable sutures can be considered for the repair of acute ATRs. Cite this article: Bone Joint J 2022;104-B(8):938–945.